Using Global South Sport-for-Development experiences to inform Global North CSR design and implementation: a case study of Euroleague Basketball's One Team programme. Issue 2 (7th April 2015) - Banda, Davies; Gultresa, Isabel
Abstract : Purpose: – The purpose of this paper is to clearly outline the practicalities of designing and implementing corporate social responsibility (CSR) through sport programmes via stakeholder involvement theory by an international governing body operating across Europe's multicultural setting. The concept of CSR and the use of sport to achieve the objectives of CSR have become common buzzwords. Within CSR, most of the academic literature, or research, has focused on defining or framing CSR through sport particularly discussing the implementation or staging of CSR activities by both sporting and non-sporting organisations. However, not much has been done regarding the practicalities of designing CSR programmes by employing stakeholder involvement theory and conducting of a thorough needs analysis before programme deployment. Design/methodology/approach: – This explorative study is based on participatory action research informed by international sport-for-development experiences. A qualitative approach was adopted in assessing the application of stakeholder involvement theory (Morsing and Schultz, 2006) in programme design and assessment of the target group's needs. Findings: – The old CSR approach was fragmented and lacked integration into local area needs. The new CSR approach ensures that community needs are reflected in CSR activities. The delivery of CSR by Euroleague Basketball professional clubs secures a licence to operate through joined-up approaches with mainstream partner agencies. These social partnerships instil a sense of community ownership of One Team Basketball projects. Originality/value: – This paper draws on lessons learnt from international sport-for-development sector where stakeholder involvement is vital for deploying development-through-sport initiatives. The paper addresses aspects which constitute sustainable developmental approaches in communities using sport CSR as a vehicle for change.